2015
DOI: 10.1016/j.brat.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance behavior in chronic pain research: A cold case revisited

Abstract: In chronic musculoskeletal pain, avoidance behavior is a prominent behavioral characteristic that can manifest itself in various ways. It is also considered a crucial component in the development and maintenance of chronic pain-related disability, supposedly fueled by pain-related fear and catastrophic beliefs. Despite the frequent occurrence of avoidance behavior and its potential impact on quality of life, relatively little research has been dedicated to the nature of avoidance in chronic pain and its assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 99 publications
(100 reference statements)
2
51
0
4
Order By: Relevance
“…25,39 Given the crucial role of avoidance in current fear-avoidance models, it is quite surprising that pain-related fear conditioning research focused primarily on self-reported and psychophysiological correlates of fear and that research on conditioned avoidance behavior is almost inexistent. 44 Therefore, we developed a novel operant conditioning procedure, better allowing for the measurement of avoidance behavior. Operant conditioning differs from classical conditioning in that it concerns learning associations between responses and their outcomes, rather than associations between stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…25,39 Given the crucial role of avoidance in current fear-avoidance models, it is quite surprising that pain-related fear conditioning research focused primarily on self-reported and psychophysiological correlates of fear and that research on conditioned avoidance behavior is almost inexistent. 44 Therefore, we developed a novel operant conditioning procedure, better allowing for the measurement of avoidance behavior. Operant conditioning differs from classical conditioning in that it concerns learning associations between responses and their outcomes, rather than associations between stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance, in contrast, leads to the maintenance or amplification of fear, which in turn results in disuse and disability. 47;242 Since its introduction, the FAM has inspired productive research and has grown to be the leading paradigm for understanding disability associated with a wide range of musculoskeletal pain conditions. Over the past decade, the original FAM has been extended to include learning, motivation, and self-regulation theory.…”
Section: Mechanism-based Pain “Models”mentioning
confidence: 99%
“…We should also note that the present article is only one in a long line of studies and classification systems that have suggested phenotyping, or clustering, patients on the basis of psychosocial characteristics, with the eventual goal of predicting treatment responses or other pain-related outcomes (e.g., disability) [24;25;45;132]. Such efforts include measurement tools such as the West Haven-Yale Multidimensional Pain Inventory (MPI, [144]), which yields empirically validated subgroups of patients [206], the Örebro Musculoskeletal Pain Screening Questionnaire [31;156], which clusters patients according to their risk for developing persistent pain, the Treatment Outcomes in Pain Survey - Short Form (S-TOPS, [117]), which phenotypes multiple physical and emotional pain-related domains, the STarT back tool, designed as a primary care screening instrument, which predicts recovery from acute back pain [124;257], as well as models such as the fear-avoidance model [59;246], and the avoidance-endurance model [120;121]. The comparison (and perhaps eventual integration) of these measures and models is unfortunately beyond the scope of the present work, but it is noteworthy that essentially all of these classification systems lean heavily on the assessment of negative affective symptoms (e.g., depression, anxiety, distress] and maladaptive pain-related cognitions [e.g., catastrophizing) [205].…”
Section: Phenotypic Domainsmentioning
confidence: 99%